Making Refuge Somali Bantu Refugees and Lewiston, Maine - Besteman, Catherine (Duke University Press, 2016)
How do people whose entire way of life has been destroyed and who witnessed horrible abuses against loved ones construct a new future? How do people who have survived the ravages of war and displacement rebuild their lives in a new country when their world has totally changed? In Making Refuge Catherine Besteman follows the trajectory of Somali Bantus from their homes in Somalia before the onset in 1991 of Somalia's civil war, to their displacement to Kenyan refugee camps, to their relocation in cities across the United States, to their settlement in the struggling former mill town of Lewiston, Maine. Tracking their experiences as "secondary migrants" who grapple with the struggles of xenophobia, neoliberalism, and grief, Besteman asks what humanitarianism feels like to those who are its objects and what happens when refugees move in next door. As Lewiston's refugees and locals negotiate co-residence and find that assimilation goes both ways, their story demonstrates the efforts of diverse people to find ways to live together and create community. Besteman's account illuminates the contemporary debates about economic and moral responsibility, security, and community that immigration provokes.This title was made Open Access by libraries from around the world through Knowledge Unlatched.
Description based on print version record.
Knowledge Unlatched Round 2
Keywords: Social Science; Political Science; Social sciences; Electronic books